2020
DOI: 10.1002/cpp.2408
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported emotion regulation difficulties in people with psychosis compared with non‐clinical controls: A systematic literature review

Abstract: Emotions play a key role in the development and experience of psychosis, yet there are important gaps in our understanding of how individuals with psychosis understand and respond to their emotions. This systematic review investigated self‐reported emotion regulation difficulties in individuals with psychosis compared with non‐clinical controls. An electronic database search was conducted in Medline, PsychINFO, and Embase and supplemented by searches of reference lists and citations. Seventeen studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 127 publications
(211 reference statements)
3
13
0
1
Order By: Relevance
“…Most research has focused on the habitual use of ER strategies and found that psychosis is associated with greater self‐reported use of more putatively maladaptive strategies (e.g., rumination) and less frequent use of a more efficacious strategy (cognitive reappraisal) compared to nonclinical controls, although there has been considerable heterogeneity of results (see Ludwig et al, 2019 for a review and meta‐analysis). Difficulties in understanding, relating and responding to emotions have received less research attention; however, research to date has found that individuals with psychosis report difficulties in relation to identifying, understanding, and accepting their emotions, engaging in goal‐directed behavior, and willingness to experience negative emotions in the pursuit of meaningful activities compared to nonclinical controls (Lawlor et al, 2020). Laboratory‐based and experience sampling method studies further indicate difficulties in tolerating distress (Chiappelli et al, 2014; Nugent et al, 2014) and in successfully identifying, selecting, and implementing ER strategies to reduce negative emotion unless individuals are instructed to do so (Horan et al, 2013; Painter et al, 2019; Perry et al, 2012; Strauss et al, 2013, 2019; Visser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has focused on the habitual use of ER strategies and found that psychosis is associated with greater self‐reported use of more putatively maladaptive strategies (e.g., rumination) and less frequent use of a more efficacious strategy (cognitive reappraisal) compared to nonclinical controls, although there has been considerable heterogeneity of results (see Ludwig et al, 2019 for a review and meta‐analysis). Difficulties in understanding, relating and responding to emotions have received less research attention; however, research to date has found that individuals with psychosis report difficulties in relation to identifying, understanding, and accepting their emotions, engaging in goal‐directed behavior, and willingness to experience negative emotions in the pursuit of meaningful activities compared to nonclinical controls (Lawlor et al, 2020). Laboratory‐based and experience sampling method studies further indicate difficulties in tolerating distress (Chiappelli et al, 2014; Nugent et al, 2014) and in successfully identifying, selecting, and implementing ER strategies to reduce negative emotion unless individuals are instructed to do so (Horan et al, 2013; Painter et al, 2019; Perry et al, 2012; Strauss et al, 2013, 2019; Visser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuals' personal accounts of their experiences of psychosis emphasize that support to deal with negative emotions and feeling less overwhelmed by emotions are important and sometimes neglected foci of psychological therapy (Greenwood et al, 2010; Griffiths et al, 2019; Holding et al, 2016; Hutchins et al, 2016; Lawlor et al, 2017). Taken together these findings suggest that further research and clinical attention is warranted however, while there are adequate measures of ER strategy use in psychosis (Ludwig et al, 2019), assessing and clinically targeting ER difficulties has been hindered by the lack of comprehensive and psychometrically sound measures for use with individuals with psychosis (Lawlor et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, el ERSQ ha sido empleado para investigar la regulación emocional tanto en población en general como en población clínica permitiendo identificar importantes diferencias. De esta manera, ha sido posible documentar los efectos de la regulación emocional en una gran variedad de procesos psicológicos entre los que destacan el trastorno de déficit de atención e hiperactividad y el trastorno límite de la personalidad (Cavelti et al, 2019), psicosis (Lawlor et al, 2020), depresión y ansiedad (Lukas et al, 2018), calidad de vida y rasgos de personalidad (Pocnet et al, 2017), apego (Owens et al, 2018), pérdida de control e impotencia (Berking et al, 2010), imagen corporal (Shriver et al, 2021, violencia de pareja (Berke et al, 2019), entre otros.…”
Section: Introductionunclassified
“…Poor regulatory flexibility is suggested to account for why some individuals are observed to have a greater tendency to rely on a narrow set of cognitive emotion regulation strategies (e.g., worry and rumination) to cope, which could increase the risk for psychopathology. Corroborating evidence shows that patients with schizophrenia spectrum disorders have poorer emotion regulation and metacognitive abilities, and these may be linked to the habitual use of worry, rumination, and expressive suppression within this population (Lawlor, Hepworth, Smallwood, Carter, & Jolley, 2019; van Camp, Sabbe, & Oldenburg, 2017). Accordingly, the habitual use of these strategies and their association with more severe positive symptoms highlight their maladaptive nature (Liu, Chua, Chong, Subramaniam, & Mahendran, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although global emotion dysregulation may overlap with maladaptive cognitive emotion regulation strategies, there is conceptual and empirical evidence to support the view that both constructs are distinct (Lawlor et al, 2019; Naragon‐Gainey, McMahon, & Chacko, 2017). From a conceptual perspective, global emotion dysregulation refers to a broad deficit in overall emotion regulation and emotional functioning, which is theoretically distinct from a strategy‐based conceptualization of emotion dysregulation (Bardeen & Fergus, 2014; Sloan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%